Minimum intervention dentistry – a new horizon in public oral health care. (31st May 2013) - Calache, H; Hopcraft, MS; Martin, JM
Abstract: Public dental patients suffer from poorer oral health than the general population. Management of dental caries tends to focus on surgical interventions, such as restorations and extractions, rather than prevention and early intervention of the disease process. The current public dental system struggles to address the lifestyle and broader health issues affecting oral health and although an immediate dental problem can usually be alleviated, it can often be through the unnecessary removal of tooth structure, which invariably leads to other health and quality of life problems. There is widespread recognition by oral health clinicians that the restorative approach to the management of dental caries in the public sector is failing to improve oral health outcomes for many public patients. Oral health experts have recently adopted a national consensus statement on minimum intervention dentistry indicating their intention to work together to develop ways to implement this approach across the public dental sector. It is clear that, despite some significant challenges and required changes, the momentum for minimum intervention dentistry continues to grow across Australia. There is an urgent need to undertake research to assess the cost‐effectiveness of this approach in the public sector.